Perancangan Ulang Tata Letak Area Produksi untuk Mengurangi Biaya Material Handling di PT.XYZ - Santoso, Angelina Jeni; Murnawan, Hery (Fakultas Teknik UMRI, 2025)
PT. XYZ is a company engaged in the printing and packaging industry, located in East Java. PT. XYZ implements a Make to Order (MTO) production system, where the production process is carried out based on customer orders. The products produced in this study include Product A, B, C up to Product I, with various sizes and types of paper according to customer requirements. This research was conducted to address the problem of high material handling costs caused by inefficient material movement distances in the production area. Therefore, a facility layout redesign (relayout) was carried out to minimize material movement distances and reduce material handling costs. The research methods involved collecting primary and secondary data, analyzing the initial layout, designing two alternative layout proposals, and conducting simulations using FlexSim software. The results showed that Layout Proposal 2 provided the best efficiency, with a reduction in total material handling costs from Rp114,491,573 to Rp84,473,414 and a decrease in total material movement distance from 2,142 meters to 1,657 meters. This relayout proved that proper facility arrangement can improve production efficiency and reduce operational costs.